Partial and total defoliation during the filling period affected grain industrial and nutraceutical quality in soybean - Carrera, Constanza Soledad; Rosas, María Belén; Gontijo Mandarino, José M.; Leite, Rodrigo Santos; Raspa, Francisco Antonio; Fava, Fernando Daniel; Dardanelli, Julio Luis; Andrade, Fernando Hector (Wiley, 2022)
BACKGROUND: Little is known about soybean grain chemical composition response to defoliation. The objectives of our study were: (i) to quantify the impact of different levels and timing of defoliation during the filling period on soybean grain yield and grain chemical content and composition, including protein, oil, fatty acids, and isoflavones; and (ii) to establish associations between them and the level and timing of defoliation. RESULTS: Yield and grain chemical components were reduced by defoliation treatments, these effects being more pronounced as defoliation increased. Mild defoliation (33%) caused small or non-significant changes in yield, its components, protein, oil, and isoflavone contents and concentrations. However, it affected oil composition, increasing the degree of unsaturation, which became more accentuated as defoliation increased. Moderate defoliation (66%) produced similar relative reductions in protein and oil contents, with small effects in isoflavone content, resulting in a generally greater isoflavone concentration in defatted flour and a greater isoflavone/protein ratio in grain. Total defoliation (100%) produced greater relative reductions in oil and isoflavone contents than in protein content. These resulted in higher protein/oil ratio and protein concentration and lower isoflavone/protein ratio and isoflavone concentration. Analyzed variables were associated with cumulative solar radiation during grain filling; indeed, this parameter successfully captured the effects of defoliation intensity and timing. CONCLUSION: By exploring different levels and timings of defoliation during the filling period, our study provides novel and important information regarding the impact of light interception decreases on grain chemical components, with special emphasis on nutraceuticals.